Genomics and physiological evolution of cold tolerance in Drosophila melanogaster - Gerken, Alison Renae (Kansas State University, 2014)
Thermal stress impacts animals around the globe and understanding how organisms adapt to changes in temperature is of particular interest under current climate change predictions. My research focuses on the evolutionary genetics involved in cold tolerance and plasticity of cold tolerance using both artificially selected and naturally segregating populations, while tying the genes of interest to their physiological components. First I address cross-tolerance of stress traits following artificial selection to a non-lethal cold tolerance metric, chill-coma recovery. Using these artificial selection populations, we found that stress traits such as desiccation tolerance, starvation tolerance, acclimation, and chronic and acute cold tolerance do not correlate with level of cold tolerance as defined by chill-coma recovery time. We next assessed lifetime fitness of these different cold tolerance lines and found that only at low temperatures did fitness differ among cold tolerance levels. We then analyzed gene expression differences between resistant and susceptible populations at three time points to understand where selection pressures are hypothesized to act on genomic variation. Our gene expression analyses found many differences between resistant and susceptible lines, primarily manifesting themselves in the recovery period following cold exposure. We next utilized a community resource, the Drosophila melanogaster reference panel, to identify naturally segregating variation in genes associated with cold acclimation and fitness. We specifically asked if long- and short-term acclimation ability had overlapping genetic regions and if plasticity values from constant rearing environments were associated with demographic parameters in fluctuating environments. We found that long- and short-term acclimation are under unique genetic control and functionally tested several genes for acclimation ability. We also found that acclimation ability in constant environments and fitness in fluctuating environments do not correlate, but that genotypes are constrained in their fitness abilities between a warm and cool environment. Our analyses describe several novel genes associated with cold tolerance selection and long- and short-term acclimation expanding our knowledge of the complex relationship between demographic components and survivorship as well as a unique investigation of the change in gene expression during cold exposure.
Keywords: Thermotolerance; Evolution; Genomics; Drosophila melanogaster; Fitness; Thermal acclimation; Biology (0306); Evolution and Development (0412); Genetics (0369)